Gender differences in self-reported morbidity: evidence from a population-based study in southern Brazil Diferenças na morbidade referida entre sexos: evidências de um estudo de base populacional no Sul do Brasil - Raúl A. Mendoza-Sassi; Jorge U. Béria (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
This paper aims to assess variations in self-reported morbidity between men and women using six different measures of reported illness. The cross-sectional study was conducted in the municipality of Rio Grande, southern Brazil. Demographic, socioeconomic, and morbidity data were collected from a probabilistic sample of 1,260 persons aged 15 years or over, using a specific questionnaire. Statistical analysis included a multivariate Poisson regression analysis. Prevalence Ratios (PR) with 95% confidence intervals (95%CI) were calculated. After adjusting for some confounding variables (age, race, unemployment, marital status, income, social class, and education), women showed greater risk of any symptom (PR = 3.21; 95%CI: 2.71-3.83), three or more symptoms (PR = 4.22; 95%CI: 2.97-5.98), potentially serious symptoms (PR = 1.75; 95%CI: 1.31-2.34), poor/fair health (PR = 1.78; 95%CI: 1.37-2.32), and minor psychiatric disorders (PR = 1.76; 95%CI: 1.31-2.37). The study revealed dissimilarity in self-reported morbidity between men and women in southern Brazil, but with different degrees depending on type of morbidity. This excess can be explained by gender difference in health-seeking behavior for perceiving or reporting health problems. O estudo teve como objetivo avaliar que diferenças ocorrem na morbidade referida entre homens e mulheres, utilizando seis medidas diferentes de morbidade. O estudo de tipo transversal foi realizado no Município de Rio Grande, Sul do Brasil. Foram coletados dados demográficos, sócio-econômicos de uma amostra probabilística de 1.260 pessoas com 15 anos ou mais. Para fins estatísticos foi utilizada a regressão de Poisson. Após ajustar para variáveis de confusão, observou-se que as mulheres apresentavam maior risco de referir um sintoma (RP = 3,21; IC95%: 2,71-3,83), de ter três ou mais sintomas (RP = 4,22; IC95%: 2,97-5,98), de ter um sintoma potencialmente sério (RP = 1,75; IC95%: 1,31-2,34), de apresentar uma percepção do estado de saúde pobre ou regular (RP = 1,78; IC95%: 1,37-2,32) e de sofrer de distúrbios psiquiátricos menores (RP = 1,76; IC95%: 1,31-2,37). O estudo aponta para a existência de diferenças entre os sexos na morbidade referida, mas com magnitudes diferentes conforme o tipo de medida de morbidade utilizada. Este excesso pode ser explicado pelas variações que ocorrem no comportamento na procura de cuidados em saúde (percepção e/ou informação de problemas de saúde) entre mulheres e homens.